(untitled) (Journal of Comparative Research in Anthropology and Sociology, 2025)
This article addresses the reverse gender gap in the performance of high school students through a case study in Ialomița County. The results show that boys face an average disadvantage compared to girls, which is a phenomenon consistently observed nationally and internationally. The study examines how the Covid-19 pandemic, gender, residence, specialization and other socio-demographic predictors contribute to educational inequalities. On one hand, it discusses the over-representation of girls in domains characterized by higher Baccalaureate graduation rates (theoretical and vocational). On the other hand, it documents the over-representation of boys in domains characterized by lower Baccalaureate graduation rates (technological). Moreover, the results indicate that high school admission and high school graduation average grades are predictors of Baccalaureate success, but they differ significantly between specialization domains. The article creates a typology of high school graduates and highlights problems related to grade inflation. These problems may hide the real competences of students, especially in the technological specialization areas. The study also notes a specific disadvantage for pupils affected by the COVID-19 pandemic.